Building Better Batteries: Solid-State Batteries with Li-Rich Oxide Cathodes - Lifeng Xu; Shi Chen; Yuefeng Su; Jizhuang He; Lian Wang; Xing Shen; Lai Chen; Duanyun Cao; Yun Lu; Meng Wang; Liying Bao; Ning Li; et al. (Energy Material Advances, 2023)
High-capacity Li-rich oxide materials have received extensive attention due to their unique anion–cation charge compensation involvement. However, the high operating voltage, poor cycling performance, unsafe oxygen evolution, and voltage decay limit their industrial application. The emergence and development of solid-state batteries offer a great opportunity to solve these issues by replacing flammable and unstable liquid electrolytes with solid electrolytes. Meanwhile, utilization of high-capacity Li-rich oxide cathodes enables to establish high-energy-density solid-state batteries with wide voltage ranges, light weight, and high mechanical properties. This review summarizes the recent progress of Li-rich oxide materials and solid electrolytes, emphasizing their major advantages, interface challenges, and modification approaches in the development of Li-rich solid-state batteries. We also propose possible characterization strategies for effective interfacial observation and analyses. It is hoped that this review should inspire the rational design and development of better solid-state batteries for application in portable devices, electric vehicles, as well as power grids.